A Cytokine Pattern That Differentiates Preseroconversion From Postseroconversion Phases of Primary HIV Infection. (1st April 2017) - Pastor, Lucia; Parker, Erica; Carrillo, Jorge; Urrea, Victor; Fuente-Soro, Laura; Respeito, Durval; Jairoce, Chenjerai; Mandomando, Inacio; Blanco, Julià; Naniche, Denise
Abstract : Background: During acute HIV infection, HIV actively replicates but seroconversion has not yet occurred. Primary HIV infection (PHI) is characterized by a transient nonspecific febrile illness, a massive inflammatory response, and the progressive appearance of anti-HIV-specific antibodies. In this study, we have identified patterns of inflammatory biomarkers associated with the innate immunological reaction before completion of a full humoral response. Methods: A symptom-based screening was used to identify acute HIV infection in the Manhiça District Hospital in Mozambique. Plasma levels of biomarkers were determined by Luminex and enzyme-linked immunosorbent assay. Anti-HIV antibodies were analyzed by flow cytometry and Western blot. Statistical analyses used random forest and logistic regression models. Results: Of 3116 rapid test seronegative or indeterminate individuals, 85 (2.7%) had positive plasma HIV viral load and were enrolled as PHI, of which n = 45 (52.9%), n = 8 (9.4%), n = 12 (14.1%), and n = 20 (23.5%) were classified as Fiebig I-III, IV, V, and VI stages, respectively, by Western blot. Comparison of individuals at early (Fiebig I-IV) and late (Fiebig V-VI) immune stages identified significant differences in the expression level of plasma B-cell activating factor, monocyte chemotactic protein-1, sCD163, and monokine induced by interferon (IFN-γ). This cytokine signature classified patients in the preseroconversion phase with a sensitivity of 92.5% and a specificity of 81.2% Conclusions: Identification of a cytokine signature specific for the preseroconversion stage of PHI may help to understand the earliest HIV pathogenic events and identify new potential targets for immunotherapy aimed at modulating the cytokine response to HIV infection. Abstract : Supplemental Digital Content is Available in the Text.